Strain-dependent induction of primary bile acid 7-dehydroxylation by cholic acid - Eduard Vico-Oton; Colin Volet; Nicolas Jacquemin; Yuan Dong; Siegfried Hapfelmeier; Karin Lederballe Meibom; Rizlan Bernier-Latmani (BMC Microbiology, 2024)
Abstract Background Bile acids (BAs) are steroid-derived molecules with important roles in digestion, the maintenance of host metabolism, and immunomodulation. Primary BAs are synthesized by the host, while secondary BAs are produced by the gut microbiome through transformation of the former. The regulation of microbial production of secondary BAs is not well understood, particularly the production of 7-dehydroxylated BAs, which are the most potent agonists for host BA receptors. The 7-dehydroxylation of cholic acid (CA) is well established and is linked to the expression of a bile acid-inducible (bai) operon responsible for this process. However, little to no 7-dehydroxylation has been reported for other host-derived BAs (e.g., chenodeoxycholic acid, CDCA or ursodeoxycholic acid, UDCA). Results Here, we demonstrate that the 7-dehydroxylation of CDCA and UDCA by the human isolate Clostridium scindens is induced when CA is present, suggesting that CA-dependent transcriptional regulation is required for substantial 7-dehydroxylation of these primary BAs. This is supported by the finding that UDCA alone does not promote expression of bai genes. CDCA upregulates expression of the bai genes but the expression is greater when CA is present. In contrast, the murine isolate Extibacter muris exhibits a distinct response; CA did not induce significant 7-dehydroxylation of primary BAs, whereas BA 7-dehydroxylation was promoted upon addition of germ-free mouse cecal content in vitro. However, E. muris was found to 7-dehydroxylate in vivo. Conclusions The distinct expression responses amongst strains indicate that bai genes are regulated differently. CA promoted bai operon gene expression and the 7-dehydroxylating activity in C. scindens strains. Conversely, the in vitro activity of E. muris was promoted only after the addition of cecal content and the isolate did not alter bai gene expression in response to CA. The accessory gene baiJ was only upregulated in the C. scindens ATCC 35704 strain, implying mechanistic differences amongst isolates. Interestingly, the human-derived C. scindens strains were also capable of 7-dehydroxylating murine bile acids (muricholic acids) to a limited extent. This study shows novel 7-dehydroxylation activity in vitro resulting from the presence of CA and suggests distinct bai gene expression across bacterial species.